2015
DOI: 10.1002/jclp.22192
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Suicidal Ideation Across Deployment: A Prospective Study

Abstract: Predeployment problem drinking may serve as a modifiable target for early intervention of suicidal ideation. Findings illuminate the compound risk of comorbid depressive symptoms and moderate problem drinking in predicting suicidal ideation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, this is the first prospective study examining the contribution of marital adjustment to SI among partners of war veterans and ex-POWs. Our results are consistent with most previous studies indicating that low marital quality and high marital distress (Robustelli et al, 2015) are related to high levels of SI, rather than those reporting no such association among veterans (e.g., Cigrang et al, 2015). It has been suggested that ex-POWS’ wives might have been compelled to take on the role of their husbands (i.e., child support, main provider) and thereby pushed aside or neglected their own needs (Zerach & Solomon, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first prospective study examining the contribution of marital adjustment to SI among partners of war veterans and ex-POWs. Our results are consistent with most previous studies indicating that low marital quality and high marital distress (Robustelli et al, 2015) are related to high levels of SI, rather than those reporting no such association among veterans (e.g., Cigrang et al, 2015). It has been suggested that ex-POWS’ wives might have been compelled to take on the role of their husbands (i.e., child support, main provider) and thereby pushed aside or neglected their own needs (Zerach & Solomon, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…However, the contribution of marital adjustment to suicidality is underresearched, with inconsistent results. Although most studies have shown that low marital quality and high marital distress (Robustelli, Trytko, Li, & Whisman, 2015) are related to high levels of SI, some studies among veterans have revealed no such association (e.g., Cigrang et al, 2015). Evidently, marital adjustment among spouses changes over the duration of the marriage.…”
mentioning
confidence: 99%
“…Our findings also indicate that the impact of nonsexual harassment is substantially greater when experienced concurrently with combat exposure, resulting in a higher risk for negative mental health outcomes—almost 4 times greater for PTSD symptoms and problem drinking and up to 6 times greater for depression. These numbers are compelling given the strong empirical support for existing associations between problem drinking, depression, and suicide (Cigrang et al, 2015). When considering studies indicating that suicide mortality ratios among female veterans are higher than in male veterans (1.87 vs. 1.66, respectively; McCarthy et al, 2009), higher in female veterans than female civilians (Kaplan et al, 2012), and are increasing (American Foundation for Suicide Prevention, 2016), it is imperative that nonsexual harassment be examined more closely.…”
Section: Discussionmentioning
confidence: 99%
“…Service members who demonstrate alcohol misuse prior to deployment are at greater risk of experiencing family-reintegration difficulties; hence, screening and early intervention regarding alcohol misuse may promote healthier family reintegration for partnered service members. In separate analyses using this same sample, predeployment alcohol misuse has also been implicated in other serious postdeployment mental health disturbances, including suicide risk (Cigrang, Balderrama-Durbin et al, 2014). Moreover, concurrent posttraumatic stress symptoms, alcohol misuse and, to a smaller degree, depressive symptoms, were all related to difficulties with family reintegration, with alcohol misuse demonstrating an incremental impact on family reintegration exceeding the effects of depressive and posttraumatic stress symptoms.…”
Section: Discussionmentioning
confidence: 99%